A Double-Blind, Placebo Controlled, Randomized Trial to Assess the Impact of a Monthly Administration of 50, 000 IU of Vitamin D3 for 6 Months on Serum Levels of 25-Hydroxyvitamin D in Healthy Young Adults. (13th November 2013) - Brunel, E.; Schnitzler, M.; Foidart-Dessalle, M.; Souberbielle, J. C.; Cavalier, E.
Abstract : In this double blind, unicentre, randomized, placebo controlled study, we evaluated the changes in 25-hydroxyvitamin D (25(OH)D) serum levels in 150 young Belgian adults (18–30 years), monthly supplemented with 50, 000 IU of vitamin D (VTD) or placebo for 6 months, from November 2010 to May 2011. At T0, 30% of the population presented 25(OH)D serum levels below 20 ng/mL. In the VTD-treated group, mean serum levels increased from 21.2 ± 8.2 to 30.6 ± 8.8 ng/mL (P < 0.001 ) at T3mo and to 36.0 ± 9.2 ng/mL (P < 0.001 ) at T6mo. Despite documented VTD intake, no changes in serum levels were, however, observed in 10% of the treated group. In the placebo group, mean 25(OH)D serum levels decreased from 22.8 ± 8.5 to 14.0 ± 6.9 ng/mL at T3mo (P < 0.001 ) but returned to values not significantly different from those observed at T0 (23.5 ± 8.6 ng/mL) at T6mo. No difference between serum calcium levels was observed between the groups throughout the study. In conclusion, monthly supplementation with 50, 000 UI of VTD in winter can warrant serum 25(OH)D levels above 20 ng/mL in 96.2% of those healthy young adults without inducing unacceptably high 25(OH)D concentration. This supplementation is safe and may be proposed without 25(OH)D testing.